Converting any surface to a touch interface - Koh, Wen Yi (2015)
In this project, optical-based touch technology is used to convert a static large display to a touch-enabled screen by making use of two wide-angle lens cameras to detect the position of the user’s finger. However, finger localisation, an essential part of the system, is inaccurate at times. After analysing the possible causes of the issue, two methods have been tried and compared to find the most effective solution. These methods are: to correct the distortion in the cameras separately, and to increase the number of calibration points.